2000
DOI: 10.1002/jor.1100180210
|View full text |Cite
|
Sign up to set email alerts
|

Use of roentgenography and magnetic resonance imaging to predict meniscal geometry determined with a three‐dimensional coordinate digitizing system

Abstract: To evaluate and improve on the procedures used by a tissue bank in selecting donor menisci for transplantation, this study was designed to fulfill four objectives: (a) define and quantify a set of independent parameters for describing the geometry of the medial and lateral menisci, (b) determine how well the sizing protocol of the tissue bank (i.e., two transverse roentgenographic measurements obtained from the injured knee or six transverse magnetic resonance imaging measurements obtained from the contralater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 19 publications
2
41
0
Order By: Relevance
“…MicroCT analysis confirmed common anatomic knowledge [ 3 , 36 , 37 ] that cross-sectional area is largest in the posterior horn (region C) followed by the anterior horn (region A), and smallest in the pars intermedia (region B). All measurements are summarized in S1 Table , and representative cross-sections for each analysed region are shown in Fig 6 .…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…MicroCT analysis confirmed common anatomic knowledge [ 3 , 36 , 37 ] that cross-sectional area is largest in the posterior horn (region C) followed by the anterior horn (region A), and smallest in the pars intermedia (region B). All measurements are summarized in S1 Table , and representative cross-sections for each analysed region are shown in Fig 6 .…”
Section: Resultssupporting
confidence: 77%
“…Both menisci (lateral and medial) are highest and widest at the posterior horn followed by the anterior horn and smallest, respectively least wide, in the pars intermedia [ 3 , 36 , 37 ] ( Fig 1 ). The results of the biomechanical properties determined at these regions did not reliably mirror these anatomic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…23 In this study, width was adequately predicted by MRI and radiography, while all but the original Pollard method accurately predicted meniscal length. These data were corroborated by Haut et al, 7 who found greater accuracy of MRI to define meniscal geometry when compared with long leg length radiography. Similarly, Prodromos et al, 13 with a study design involving contralateral long leg length radiographs, also concluded that MRI should be considered the gold standard.…”
Section: Discussionsupporting
confidence: 57%
“…Some authors defend that direct measurements of the meniscal size with MRI are more accurate than indirect measurements with plain X-ray or computed tomography [ 9 , 31 ]. MRI of the contralateral, non-injured side is an alternative to direct measurement of the meniscal dimensions before transplantation.…”
Section: Discussionmentioning
confidence: 99%